Enhancing purchase intention of electric vehicle: implementing theory of planned behavior and green purchase behavior - Andre Tanuwijaya; Tengku Ezni Balqiah (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The development of sustainable energy in Electric Vehicles (EV), is highly dependent on customer perceptions of purchase intentions (EV). The purpose of this study is to identify the motivations that influence the purchase intention of EVs either directly or indirectly by using product attribution, theory of planned behavior, green purchase behavior, and purchase intention with environmental consciousness as moderation. To test the 13 hypotheses, data were collected using a quantitative survey design, and 826 respondent’s car users in Jabodetabek were selected using the purposive sampling method, and processed using the Structural Equation Modeling (SEM) method to examine the direct, indirect, and moderating effects, as well as multi-group SEM to test the effect of purchase intention based on income group. The results of processing the data show that there are 12 accepted hypotheses, which show that there is an indirect effect of product attribution and a direct effect of the theory of planned behavior and green purchase behavior on EV purchase intention. Furthermore, there is a moderating effect of environmental consciousness in influencing purchase intention, and it is found that there are differences in purchase intentions based on income group. This finding will assist policymakers in adopting effective variables to set the overall communication strategy as well as in EV segmentation to build potential purchase intentions of electric cars in a structured manner.